SISTEM PENDUKUNG KEPUTUSAN SELEKSI PEMILIHAN PERGURUAN TINGGI MENGGUNAKAN METODE TOPSIS - Hertyana, Hylenarti (Jurnal Pilar Nusa Mandiri, 2019)
High school alumni of the same level often experience difficulties in determining universities to continue their studies. The selection of tertiary institutions for equivalent high school alumni is constrained only by listening to talk, even often because of following friends. This is because there are so many types of criteria from universities that eventually make prospective students confused and choose without consideration. The selection of higher education institutions should be adjusted between the criteria of higher education and the needs and abilities of prospective students. This study uses an experimental model regarding the selection system of higher education selection decisions using the TOPSIS method. The purpose of this study is to help prospective students in the selection of universities to continue their studies. 7 criteria were obtained including Cost (BY) obtained from tuition fees, Accreditation Value (NA) obtained from the value of college accreditation, Achievement (PS) obtained from academic and non academic achievements, Lecturer Education (PD) obtained from education lecturers, facilities (FS) obtained from available facilities, scholarships (BS) obtained from scholarships at tertiary institutions and UKM (UK) obtained from student activity units available at the college. The results of this study can meet the objectives because the results of calculations can be faster in producing information that can help prospective students in choosing a college.